Time-motion analysis and physiological responses of small-sided team handball games in youth male players: Influence of player number - Jan Bělka; Karel Hůlka; Michal Šafář; Lada Dušková; Radim Weisser; Václav Riedel (Palacký University Olomouc, 2016)
Background: Effective training depends on knowledge of a sport's requirements. Small-sided games (SSG) are a spontaneous form of specific training, where exercise intensity can be manipulated mainly by modifying external factors. In SSG the players develop technical and tactical skills in the similar situations, such as during a match and can also develop their physical skills. Objective: The purpose of this study was to examine the distance covered and physiological response of altering the number of youth male players during small-sided team handball games with modified rules. Methods: The subjects consisted of 12 male youth team handball players (age 16.6 ± 0.5 years) playing the first league for youth male players in the Czech Republic. The study was conducted during six weeks (one training session per week). Only three SSG were played in each training session. The SSG were played, first with five players on each side (5 vs. 5), then four (4 vs. 4), then three (3 vs. 3). Each game was four minutes long, followed by three minutes of passive rest. Results: The players covered the greatest distance (520.6 ± 61.4 m) in the SSG 3 vs. 3. There was a difference in the distance covered between players in the 3 vs. 3 SSG and the other SSG (4 vs. 4 and 5 vs. 5) (p = .041 and p = .043, respectively). In individual speed zones a difference occurred only in the first and third speed zone and always among the 3 vs. 3 and 5 vs. 5 SSG (p = .034 and p = .044), respectively. The highest average intensity (87.9 ± 4.8% HRmax) was in 3 vs. 3 SSG. Loading of the players in 5 vs. 5 was lower compared to 4 vs. 4 (p = .035) and 3 vs. 3 (p < .001). There was a difference in zone load intensity (> 90% HRmax) between 3 vs. 3 and 5 vs. 5 SSG (p = .041). Conclusions: These results indicate that changing the number of players during SSG with modified rules in youth team handball may be used to manipulate the physiological response during youth team handball training.